Knowledge and beliefs about dementia among the general public: A preliminary report on the Cuban population - Y. Broche-Pérez; Z. Fernández-Fleites; B. González; M.A. Hernández Pérez; Y.I. Salazar-Guerra (Neurología (English Edition), 2021)
Background: The number of people diagnosed with dementia globally has dramatically increased in recent years. The objective of this study was to explore beliefs and knowledge among the Cuban population with regard to the risk factors that may lead to dementia and the actions that may be taken to prevent it. Method: In an exploratory cross-sectional study, we surveyed a total of 391 people aged between 18 and 96 years. The results were stratified by sex, age range, level of education, and contact with dementia. Results: Dementia was the fourth most worrying disease. A total of 64.5% of participants believed that the risk of dementia could be reduced, and 60% that the appropriate time to begin prevention measures is after the age of 40. Cognitive stimulation and healthy diet were more frequently cited as useful activities to reduce risk. Survey respondents reported little presence in their lifestyle of behaviours that are beneficial for reducing the risk of dementia. Conclusions: Although dementia is an important health issue for respondents, their knowledge about disease prevention is still insufficient. The results obtained constitute a starting point for the design of policies aimed at increasing knowledge about the disease and improving prevention. Resumen: Introducción: El número de personas diagnosticadas con demencia a escala global se ha incrementado drásticamente en los últimos años. El propósito del presente estudio fue explorar las creencias y el conocimiento existente en la población cubana sobre los factores de riesgo que pueden conducir a la demencia y las acciones que pueden llevarse a cabo para su prevención. Método: Se realizó un estudio exploratorio transversal. Se encuestó a 391 personas, con un rango de edad entre los 18 y 96 años. Los resultados se estratificaron atendiendo a las variables sexo, rango de edad, escolaridad y contacto con demencia. Resultados: La demencia se ubicó como la cuarta enfermedad más preocupante para los participantes. El 64,5% consideró que el riesgo de demencia podía ser reducido y el 60% que la edad idónea para iniciar la prevención es posterior a los 40 años. La estimulación cognitiva y la dieta saludable fueron señaladas con más frecuencia como actividades útiles para reducir el riesgo, existiendo además poca presencia en el estilo de vida de los encuestados, de comportamientos que resultan beneficiosos para la reducción del riesgo de presentar demencia. Conclusiones: La investigación constató que aunque la demencia constituye un tema de salud importante para los encuestados, todavía no se tiene suficiente conocimiento sobre las acciones a realizar para reducir el riesgo de presentarla. Los resultados obtenidos constituyen un punto de partida para el diseño de políticas dirigidas a potenciar el conocimiento sobre la demencia y su prevención.